(untitled) (Annals of Medical Research, 2021)
Aim: Inflammatory bowel diseases (IBD) including ulcerative colitis (UC) and Crohn’s disease (CD) are chronic inflammatory diseases of the gastrointestinal tract. An increase in thromboembolic complications has been observed among patients with IBD. Platelet activation and aggregation play an important role in the pathophysiology of atherotrombosis. Mean platelet volume (MPV), a determinant of platelet activation, is one of the newly identified risk factors for atherothrombosis. In this study, we investigated the possible relationship between IBD and MPV.